Pengaruh Insiden di Tempat Kerja terhadap Perilaku Kerja Inovatif dengan Kecemasan Kerja sebagai Mediasi pada Usaha Kreatif di Banyumas - Adisti, Dinar Adisti; Kurniasih, Retno Kurniasih (ICON Publisher, 2025)
This study aims to analyze the effect of workplace incivility on innovative work behavior mediated by job anxiety in Micro, Small and Medium Enterprises (MSMEs) engaged in creative businesses in Banyumas. The type of research used in this study is quantitative research using a questionnaire as a tool to obtain data. This study used a sample of 40 samples. The sampling technique used in this study was purposive sampling and tested using Statistic Product and Service Solution (SPSS) 23 software. Based on the results of the study and data analysis, it shows that workplace incivility has a significant negative effect on innovative work behavior, job anxiety has no effect on innovative work behavior, workplace incivility does not affect job anxiety, and job anxiety does not mediate the relationship between workplace incivility and innovative work behavior. The results of the study indicate that workplace incivility can be considered a drain on resources that leads to a decrease in innovative work behavior. This study is expected to be a material that is introduced to build and support a positive and safe work environment from negative events in the work environment.